2010
DOI: 10.1161/strokeaha.110.589275
|View full text |Cite
|
Sign up to set email alerts
|

Definition of Delayed Cerebral Ischemia After Aneurysmal Subarachnoid Hemorrhage as an Outcome Event in Clinical Trials and Observational Studies

Abstract: Background and Purpose-In clinical trials and observational studies there is considerable inconsistency in the use of definitions to describe delayed cerebral ischemia (DCI) after aneurysmal subarachnoid hemorrhage. A major cause for this inconsistency is the combining of radiographic evidence of vasospasm with clinical features of cerebral ischemia, although multiple factors may contribute to DCI. The second issue is the variability and overlap of terms used to describe each phenomenon. This makes comparisons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
938
0
15

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,265 publications
(1,010 citation statements)
references
References 49 publications
11
938
0
15
Order By: Relevance
“…Microthromboembolism, cortical spreading ischemia, delayed effects of acute SAH-induced brain injury, and impaired cerebral autoregulation have been suggested to have a role in clinical outcome (Vergouwen et al, 2008;Dreier et al, 2009;Yundt et al, 1998). Since cerebral infarction is the ultimate outcome of DCI, it has been suggested that cerebral infarction is a better outcome measure in observational studies and clinical trials than vasospasm (Vergouwen et al, 2010). The findings of the present study support this suggestion.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…Microthromboembolism, cortical spreading ischemia, delayed effects of acute SAH-induced brain injury, and impaired cerebral autoregulation have been suggested to have a role in clinical outcome (Vergouwen et al, 2008;Dreier et al, 2009;Yundt et al, 1998). Since cerebral infarction is the ultimate outcome of DCI, it has been suggested that cerebral infarction is a better outcome measure in observational studies and clinical trials than vasospasm (Vergouwen et al, 2010). The findings of the present study support this suggestion.…”
Section: Discussionsupporting
confidence: 77%
“…The findings of the present study support this suggestion. Obviously, the main outcome measure in such studies should be functional outcome (Vergouwen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors thus concluded that there was no evidence from animal studies that treatment with an endothelin receptor antagonist improved clinically relevant outcomes after SAH, while the reduction in cerebral vasospasm observed in animal studies was consistent with that observed in clinical trials, an effect that was not associated with better functional outcome in patients [30]. The different outcomes between experimental and clinical studies may also occur due to misinterpretation of data and confused terminology and definitions [31]. Anyway, we can say that the failed clinical trials could have been predicted and avoided if the review and the meta-analysis had been performed before planning the clinical trials.…”
mentioning
confidence: 94%